SPIRITUALITAS UNTUK MEWUJUDKAN LINGKUNGAN KERJA POSITIF DAN MOTIVASI INTRINSIK - Caroline Lauw (Jurnal Akuntansi dan Keuangan, 2022)
This study intends to provide an overview the implications of spiritual values in management control system (MCS) of organizational culture and employee care center towards intrinsic motivation and spirituality at workplace. This study uses the case study method to see and interpret social phenomena. Data collected through interview, observation, and document analysis. Research concludes that MCS instill spiritual values could build a work environment and shared experience, also brings positive influence on spirituality at work. Spirituality eliminates competition, build teamwork, and increase opportunities to learn and grow together as a community. Employees responded positively to company's growth as an opportunity to have greater goals, contribute to make company better, and self-actualize that brings satisfaction and happiness. Money is no longer a motivation to work better and stay in company, but employees look for opportunities and support to be involved, contribute, and develop themselves.